Evaluation of the effectiveness of oral awareness programs using the knowledge, attitude, and practice study among the Anganwadi workers in Ponnani Block Panchayat: An exploratory study - Joby Peter; Vijai Shivappa; Krishna Kumar; Melvin Augustin; Tinet Mary Agustine; Ambili Vijay Kumar (Wolters Kluwer Medknow Publications, 2017)
Introduction: One of the main reasons for the oral diseases among the children of rural population in a country like India is the inadequate knowledge of the care givers. Attitude towards the oral health and practical approaches about the various oral hygiene measures should be checked and guided by the health providers. Anganwadi workers are the grass root workers who interact with the children and their mothers of their respective work areas with equal importance. So guiding them is indirectly guiding these populations. Aim and Objective: The aim of this paper is to assess the knowledge, attitude and practice of the Anganwadi workers about the child's oral health and also to evaluate effectiveness of the awareness programs in guiding these early care providers. Material and Methods: The study was conducted among the Anganwadi workers of the Ponnani Block Panchayat situated in Edappal ,Malappuram District, Kerala. A total of 15 questions were prepared in regional language (Malayalam) and were given before and after the awareness class session. Awareness class session was conducted using the audio visual aids including PowerPoint presentation and videos. The awareness classes included the topics of child oral health facts and various practical approaches. Statistical Analysis: A paired t-test was conducted and the results were analyzed using the SPSS version 20. Results: The total value before the session was changed from 7.91±2.15 to the after session value of 12.28±1.67 (P value <0.001) indicating a statistically significant shift after the awareness class. Discussion: The comparison of separate sessions of knowledge, attitude and practice is evaluated using the boxplot evaluation and the effectiveness of the awareness class was plotted using the Receiver operating characteristic (ROC) Curve. Conclusion: The study revealed the need of incorporation of more awareness programs among the early care givers regarding a child oral health to improve their knowledge and to incorporate a positive attitude and guide them to practically prevent various oral diseases.